First record of the tarantula genus euathlus (Araneae: Theraphosidae: Theraphosinae) in Peru, with the description of a threatened new species - Quispe Colca, Oscar (2021)
A new species of Euathlus Ausserer, 1875 (Araneae: Theraphosidae: Theraphosinae), Euathlus vanessae sp. nov. is described and diagnosed. The genus is known from Chile and Argentina, and E. vanessae sp. nov. represents the first record for the genus in Peru, being the new northernmost limit of its known distribution. Distribution and natural history data are provided. Additionally, the conservation status of the new species is discussed and it is proposed as Endangered (EN) according to IUCN criteria.